Pregnancies and live births after 20 transplantations of cryopreserved ovarian tissue in a single center - Dittrich, Ralf; Hackl, Janina; Lotz, Laura; Hoffmann, Inge; Beckmann, Matthias (Fertility and Sterility, 2015)
To report the results of 20 orthotopic retransplantations of cryopreserved ovarian tissue after cancer treatment.Retrospective analysis.Tertiary gynecology department.Twenty patients with malignant disease: 11 with hematological malignancies (55%), four with breast cancer (20%), three with anal cancer (15%), and two with ovarian cancer (10%); the mean age before oncological treatment was 30.5 years.Ovarian tissue was removed from patients in various centers in Germany in 2005-2009. All patients received chemotherapy and/or radiotherapy. Afterward, 17 patients had complete premature ovarian insufficiency, while three still showed some ovarian activity. Overnight transportation of tissue before freezing was necessary in eight cases. Cryopreservation followed slow freezing protocols in all cases. Retransplantation was performed at Erlangen University Hospital 3.75 years after extraction, on average. Thawed tissue was transplanted into a peritoneal pouch in the broad ligament region, below the tube, in 16 cases. Fragments were sutured both onto the remaining ovary and into a peritoneal pouch in four cases.Restoration of ovarian activity, pregnancy, birth.Ovarian activity resumed in all patients except one. Seven patients conceived, with one miscarriage and four ongoing pregnancies. Four patients delivered healthy babies. One pregnancy and live birth after oocyte donation need to be considered separately.These data clearly demonstrate that preserving fertility by cryopreserving ovarian tissue is a successful and safe clinical option that can be considered for selected cancer patients.
EVALuna2:17542